FACE-NEGOTIATION ANTARA KOMUNITAS SUPORTER TIM SEPAK BOLA YOGYAKARTA BCS DAN BRAJAMUSTI DALAM KOMUNIKASI ANTARPRIBADI DI LUAR MATCH - Rivga Agusta (Jurnal Ilmu Komunikasi AKRAB, 2018)
The fanaticism of supporters of the pride of the football team in each region often causes trouble outside the “field”. This kind of fanaticism also occurs between two supporters of the football team in Yogyakarta, namely the Brigata Curva Sud (BCS) community and Brayat Jogja Utama Sejati (Brajamusti). Although they have long experienced "friction", the two communities that live in one area of Yogyakarta establish a communication that is quite different when it is outside the scope of the match. Not a few of them turned out to have close and even friendly relationships despite defending different football teams. This article examines the interpersonal communication that exists between members of the two BCS and Brajamusti communities in the outside of the match. Specifically the findings in the field were analyzed by the face-negotiation theory. The study was carried out using explanatory case study methods. The results of this study indicate that the two supporter communities namely BCS and Brajamusti have the same tendency in dealing with conflicts that occur in their interpersonal communication, namely by avoiding strategies, and including the type of self-maintenance maintenance with face restoration strategies.